2009
DOI: 10.1021/jo900271x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Chemoenzymatic Synthesis of Chiral Pincer Ligands

Abstract: Chiral, nonracemic pincer ligands based on the 6-phenyl-2-aminomethylpyridine and 2-aminomethylbenzo[h]quinoline scaffolds were obtained by a chemoenzymatic approach starting from 2-pyridyl and 2-benzoquinolyl ethanone. In the enantiodifferentiating step, secondary alcohols of opposite absolute configuration were obtained by a baker's yeast reduction of the ketones and by lipase-mediated dynamic kinetic resolution of the racemic alcohols. Their transformation into homochiral 1-methyl-1-heteroarylethanamines oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…According to our studies on Ru and Os complexes, which showed that (S,R)-Josiphos is correctly matched with the chiral RPyme and CNN ligands of R configuration, we prepared derivative 6 by reaction of [OsCl 2 (PPh 3 ) 3 ] with the bulkier (S,R)-Josiphos* diphosphane and ligand (R)-b, obtained from 1-(benzo[h]quinolin-2-yl)ethanone via lipase-mediated kinetic resolution of the corresponding racemic secondary alcohol. [14] Complex 6 was obtained as a single stereoisomer, as confirmed by 31 P NMR spectroscopy, and isolated in 64 % yield.…”
Section: Synthesis and Characterization Of [Oscl(cnјn)(pp)] Complexesmentioning
confidence: 81%
See 1 more Smart Citation
“…According to our studies on Ru and Os complexes, which showed that (S,R)-Josiphos is correctly matched with the chiral RPyme and CNN ligands of R configuration, we prepared derivative 6 by reaction of [OsCl 2 (PPh 3 ) 3 ] with the bulkier (S,R)-Josiphos* diphosphane and ligand (R)-b, obtained from 1-(benzo[h]quinolin-2-yl)ethanone via lipase-mediated kinetic resolution of the corresponding racemic secondary alcohol. [14] Complex 6 was obtained as a single stereoisomer, as confirmed by 31 P NMR spectroscopy, and isolated in 64 % yield.…”
Section: Synthesis and Characterization Of [Oscl(cnјn)(pp)] Complexesmentioning
confidence: 81%
“…The solvents and ketones were carefully dried by standard methods and distilled under argon before use. The Josiphos diphosphanes were purchased from Aldrich, whereas ligands a, [11] b, [14] and complexes [OsCl 2 (PPh 3 ) 3 ] [18] and 1-4 [11] were prepared according to literature procedures. NMR spectroscopic measurements were recorded with a Bruker AC 200 spectrometer, and chemical shifts (in ppm) are relative to TMS for 1 H and 13 C{ 1 H} and 85 % H 3 PO 4 for 31 P{ 1 H}.…”
Section: Methodsmentioning
confidence: 99%
“…Since the pioneer work of Bäckvall (Larsson et al, 1997;Persson et al, 1999), 1 has been applied to the DKR of a wide range of substrates (Atuu and Hossain, 2007;Felluga et al, 2009;Hoyos et al, 2006Hoyos et al, , 2008Hoyos et al, , 2011aHoyos et al, , 2011bHuerta et al, 2000;Jung et al, 2000aJung et al, , 2000bKiełbasiński et al, 2005;Kim et al, 2001;Millet et al, 2010;Pàmies and Bäckvall, 2001, 2002a, 2002bRunmo et al, 2002;Strübing et al, 2007;Vallin et al, 2009;Verzijl et al, 2005) and new Ru (II)-based racemization catalysts compatible with lipases were discovered and developed, many of which are free from some drawbacks exhibited by 1 in DKR reactions, such as: the need for high temperatures, long reaction times and, in some cases, requirement of additives such as the substrate corresponding ketone (Larsson et al, 1997;Persson et al, 1999) or hydrogen sources to minimize substrate oxidation Pàmies and Bäckvall, 2002a;Runmo et al, 2002); incompatibility with the use of alkenyl esters such as vinyl acetate (Larsson et al, 1997;Persson et al, 1999) and instability under aerobic conditions. Several complexes of Ru (II) have been combined with lipases for DKR of alcohols, some of which are depicted in Fig.…”
Section: Dynamic Kinetic Resolution Of Secondary Alcohols and Derivatmentioning
confidence: 99%
“…In addition to the aforementioned examples, a wide variety of optically pure hydroxylated compounds have been obtained by dynamic kinetic resolution co-catalyzed by lipases and Ru (II) complexes, including benzyl and aliphatic alcohols, diols, hydroxyesters, hydroxyamides, α-hydroxy ketones and benzoins (Agrawal et al, 2014;Felluga et al, 2009;Hoyos et al, 2006Hoyos et al, , 2008Hoyos et al, , 2011aHoyos et al, , 2011b.…”
Section: Dynamic Kinetic Resolution Of Secondary Alcohols and Derivatmentioning
confidence: 99%
“…Baker's yeast has been also shown to be a useful catalyst in the preparation of alcohol (S)-211 using ketone 210 as starting material (Scheme 41b). 176 Subsequent transformation of the hydroxyl group into amine yielded the pincer ligand (S)-212 in enantiopure form. This type of compound complexed with Os and Ru are useful catalysts in the enantioselective transfer hydrogenation of prochiral ketones.…”
Section: Scheme 40mentioning
confidence: 99%